2001
DOI: 10.1016/s0014-5793(01)02311-0
|View full text |Cite
|
Sign up to set email alerts
|

PKC phosphorylation of a conserved serine residue in the C‐terminus of group III metabotropic glutamate receptors inhibits calmodulin binding

Abstract: Group III metabotropic glutamate receptors (mGluRs) serve as presynaptic receptors that mediate feedback inhibition of glutamate release via a Ca 2+ /calmodulin (CaM)-dependent mechanism. In vitro phosphorylation of mGluR7A by protein kinase C (PKC) prevents its interaction with Ca 2+ /CaM. In addition, activation of PKC leads to an inhibition of mGluR signaling. Here, we demonstrate that disrupting CaM binding to mGluR7A by PKC in vitro is due to phosphorylation of a highly conserved serine residue, S862. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
58
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 23 publications
4
58
0
Order By: Relevance
“…The results presented here show that mGluR 7A and Ca 2ϩ /CaM form a classical wraparound CaM⅐receptor complex with a 1:1 stoichiometry and a basic 1-8-14 receptor-binding motif similar to that found in smooth muscle myosin light chain kinase. In addition, our structural data indicate that Ca 2ϩ /CaM binding to mGluR 7A includes interactions with both Ser 862 , a target site for phosphorylation by protein kinase C (13,24,25), and the G␤␥ recognition motif, and thus support the view that CaM regulates signal transduction in an activity-dependent manner by competition for receptor-binding sites (15).…”
supporting
confidence: 74%
See 2 more Smart Citations
“…The results presented here show that mGluR 7A and Ca 2ϩ /CaM form a classical wraparound CaM⅐receptor complex with a 1:1 stoichiometry and a basic 1-8-14 receptor-binding motif similar to that found in smooth muscle myosin light chain kinase. In addition, our structural data indicate that Ca 2ϩ /CaM binding to mGluR 7A includes interactions with both Ser 862 , a target site for phosphorylation by protein kinase C (13,24,25), and the G␤␥ recognition motif, and thus support the view that CaM regulates signal transduction in an activity-dependent manner by competition for receptor-binding sites (15).…”
supporting
confidence: 74%
“…The mGluR 7A sequence is unusual in that instead of a basic residue a serine (Ser 862 ) precedes the phenylalanine, which is the site of phosphorylation by protein kinase C (13,24). Phosphorylation at equivalent sites in other binding sequences has been shown to greatly reduce the affinity for Ca 2ϩ / CaM.…”
Section: Structural Analysis Of the Mglur 7a-c Cam Interaction-mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has demonstrated that CaM binding to the receptor third intracellular loops can attenuate the interactions between G␣ i and several receptors, including the 5-HT 1A receptor (36), -opioid receptor (34), D 2 dopamine receptor (33), and the group III metabotropic glutamate receptor, mGluR7a (66,67). New evidence in the current report suggests that CaM binding to the second intracellular loop of the 5-HT 2A receptor likely modulates coupling to heterotrimeric G proteins, most likely G␣ q/11 and/or G␣ 12/13 subunits.…”
Section: Discussionmentioning
confidence: 99%
“…PKC phosphorylated Ser-881 in mGluR5, located in the PP1␥1/2 binding motifs identified in this study. PKC was also linked to mGluR7b via PICK1 (27), and PKC phosphorylation of the proximal C-terminal domain, identical between mGluR7a and mGluR7b, was shown (51).…”
Section: Discussionmentioning
confidence: 99%